Synthesis Of Novelthiazoles Containing Pyrazolone Systems And Antimicrobial Acivity - L.K.RAVINDRANATH; E.V.SURESH KUMAR; K.SRIKANTH Y.N.SPOORTHI; P.PHEBE (International Journal of Pharma and Bio Sciences, 2012)
Several thiazoles and pyrazolone carrying heterocyclic nucleus were synthesized and tested as antimicrobial agents. All compounds and some of the nitro substituted derivatives have effective antibacterial properties against Gram positive bacteria (Staphylococcus aureus NCCS 2079 and Bacillus cereus NCCS 2106), Gram negative bacteria (Escherichia coli NCCS 265 and Pseudomonas aeruginosa NCCS2200). The antifungal activity of synthesized compounds were studied by disc diffusion method against the organisms of Aspergillus niger NCCS 1196 and Candida albicans NCCS 3471. The chemical structures of these newly synthesized compounds were characterized by 1H-NMR, Mass, and IR spectral data.